Tackling international tax avoidance: If South Africa has general anti-avoidance rules, why does it need the principal purpose test? - Opperman, Marine (Department of Commercial Law, 2022)
The OECD's MLI was tabled for signature on 7 June 2017 and South Africa was amongst the first 68 countries to sign the MLI on that date. With its signature, South Africa made the provisional selection to adopt the PPT minimum standard, which was introduced by the OECD's Final Report on BEPS Action 6. This minimum standard effectively incorporates a treaty GAAR into South Africa's treaties that are covered under the MLI. However, South Africa already has a very comprehensive and complicated domestic GAAR. In their review of the OECD's Final Report on BEPS Action 6, the Davis Tax Committee observed that the GAAR and the PPT serve a similar purpose and that the GAAR can be applied to prevent the abuse of treaties. They stated further, that one could therefore argue that there is no need for South Africa to amend its treaties to include the PPT. Nevertheless, as much as the OECD Final Report on BEPS Action 6 clearly explains that domestic law provisions can be applied to prevent treaty abuse, there could be concerns of treaty override if South Africa applies its GAAR in a treaty context. This dissertation's objective was to investigate the Davis Tax Committee's propositions noted above. An in depth analysis and comparison of the GAAR and the PPT resulted in the conclusion that the Davis Tax Committee's propositions were correct. The core purpose and functions of the GAAR and PPT are similar to the extent that the GAAR could be applied to prevent treaty abuse, instead of the PPT. The South African legal framework is further set up in such a way that the GAAR can not only be legally applied in a treaty context, but that it would trump a treaty provision in the event of an irreconcilable clash, which results in the Davis Tax Committee's concern for treaty override. Despite the conclusion that the GAAR may replace the PPT, it may not be practical for South Africa to apply its GAAR in a treaty context and it was concluded that it is highly unlikely that South Africa would substitute the PPT for the GAAR.